PERKEMBANGAN PENELITIAN LIFE CYCLE DALAM KAJIAN LIFE CYCLE COST DAN RENOVASI BANGUNAN: STUDI BIBLIOMETRIK - Risa Nur Elga; Dewi Yustiarini; Naufal Ariq Pratama (Construction and Material Journal, 2026)
This study aims to map the development of Life Cycle Cost (LCC) research in building management and to identify the position of renovation strategies within life cycle–based research structures. A bibliometric approach was applied using Scopus-indexed publications from 2016 to 2026. After screening, 94 relevant articles were analyzed using VOSviewer to examine co-citation networks, publication trends, and keyword co-occurrence patterns. The findings show a significant increase in LCC-related publications since 2019, particularly in journals focusing on energy performance and building sustainability. Keyword network analysis identifies life cycle as the central concept, strongly linked to energy efficiency, costs, life cycle assessment (LCA), and building renovation. The linkage strength of building renovation reaches 41.7% relative to the centrality of life cycle, indicating that renovation has been integrated into life cycle research but has not yet become a dominant theme. Overall, existing studies predominantly emphasize cost evaluation across the building lifespan, with limited integration of physical intervention strategies. These results highlight the need to develop more integrative LCC models that explicitly incorporate renovation strategies as part of sustainable long-term building management.